The development and implementation of electronic gambling machine policy: a qualitative study of local government policy makers. (22nd July 2020) - Marko, Sarah; Thomas, Samantha L.; Pitt, Hannah; Daube, Mike
Abstract: Objective: To understand how policies developed by Local Government Authorities (LGAs) to address electronic gambling machine (EGM) harm are developed and implemented. Methods: Semi‐structured interviews were conducted with 16 participants from 15 LGAs in metropolitan Melbourne who worked in a role associated or aligned with gambling. An inductive thematic analysis was used to interpret the data. Results: Three key themes emerged. First, participants described a shift from addiction frameworks to public health policy responses to EGMs, which was driven by increasing EGM losses and the harms caused by EGMs to communities. Second, there was the role of stakeholder groups in the policy‐making process, including the challenges associated with engaging the community. Finally, there were barriers and facilitators to policy development and implementation. Barriers included a lack of financial resources and legislative boundaries imposed by the State Government. Facilitators included whole‐of‐LGA approaches, supportive councillors and collaborative efforts. Conclusions and implications for public health: LGAs have made shifts towards public health responses to EGM harm. Initiatives to further support policy development and implementation could include imposing a levy on EGM losses to directly support public health prevention activities and implementing robust state‐based regulatory frameworks that support LGA responses to EGM harm.